A novel reconfiguration procedure to extract maximum power from partially-shaded photovoltaic arrays. (October 2018) - Akrami, Mohammadreza; Pourhossein, Kazem
Highlights: A novel procedure (PCT) is proposed to reconfigure partially shaded PV arrays. The proposed procedure finds both optimal reconfiguration and absolute MPP. This procedure is based on removal of right-hand local peaks of MPP using PCI index. Due to removal of right-hand peaks of absolute MPP, it is impossible to fall in local MPPs. This procedure is simple and easy-to-implement. Abstract: This paper presents a new reconfiguration procedure, named power comparison technique (PCT), to extract maximum power from photovoltaic arrays. PCT introduces optimum configuration and maximum power point (MPP) of photovoltaic arrays in partial shading conditions. PCT finds absolute MPP and its corresponding configuration via comparing whole peaks of power-voltage (P-V) curve of a photovoltaic (PV) array. This will ensure that the right-hand peaks of absolute MPP have been removed. This logic comes to help algorithm of MPP tracking to identify the absolute peak. This approach is applicable for any topology of PV arrays (series-parallel and total-cross-tied, here). Simulations show better (or at least equal) reconfiguration results by the proposed method in comparison to the previous works reviewed. Results represent about 8% increase in mean output power based on the studied cases.